Between Integrity and Temptation: Rural Women’s Roles in Local Governance and Corruption Risks - Budirahayu, Tuti; Ariadi, Septi; Sudarso, Sudarso; Rahayu, Endah; Mawardi, Rafi Aufa (UIN Sunan Ampel Surabaya, 2025)
Corruption in Indonesia, especially in government, is often associated with structural and cultural factors that contribute to corruption. This study aims to describe the knowledge of women in rural areas who play a role in both local government and social activities that intersect with local government in dealing with various corrupt practices that can occur in village government structures. The research approach is quantitative with a descriptive research type. Data were collected by interviewing 50 women who live in Menganti Village, Gresik Regency, East Java. Most of the women who were respondents worked as village government officials and village cadres who ran village government programs. This study began by giving questionnaires to respondents about their understanding of matters related to village fund management and corrupt practices. The second stage, in-depth interviews and observations related to their daily activities, were conducted. The study results showed that 78% of respondents understood corrupt acts, such as abuse of authority and embezzlement. However, 64% admitted to experiencing social or political pressure that influenced their decisions in maintaining integrity. As many as 52% of respondents stated that weak transparency and minimal supervision from the community opened up opportunities for corruption. Meanwhile, 60% of respondents said that rationalization practices—such as considering corrupt acts as “commonplace” in the bureaucracy—still occur in their environment. These findings confirm that although village women know about corruption, their decisions are still heavily influenced by the local social and political context. In addition, the lack of literacy among the general public regarding village fund management also strengthens the occurrence of maladministration and corruption practices at the local level.